Linear fixed-effects estimation with non-repeated outcomes - Helmut Farbmacher; Harald Tauchmann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2021)
This paper demonstrates that popular linear fixed-effects panel-data estimators are biased and inconsistent when applied in a discrete-time hazard setting - that is, one in which the outcome variable is a binary dummy indicating an absorbing state, even if the data-generating process is fully consistent with the linear discrete-time hazard model. In addition to conventional survival bias, these estimators suffer from another source of - frequently severe - bias that originates from the data transformation itself and, unlike survival bias, is present even in the absence of any unobserved heterogeneity. We suggest an alternative estimation strategy, which is instrumental variables estimation using first-differences of the exogenous variables as instruments for their levels. Monte Carlo simulations and an empirical application substantiate our theoretical results.
Keywords: C23; C25; C41; 330; linear probability model; individual fixed effects; discrete-time hazard; absorbing state; survival bias; instrumental variables estimation